2019
DOI: 10.1016/j.jsxm.2019.03.266
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction and Satisfaction in Kidney Transplant Patients

Abstract: Introduction 10% of the world’s population suffers from chronic kidney disease. Kidney transplants provide an improvement in the quality of life of those patients. Sexual dysfunction is common after kidney transplantation, and its etiology is presumed to be multifactorial. It has a negative impact on sexual satisfaction and health-related quality-of-life. The integration of a new organ into the body can imply an adjustment of body image, which may eventually have a negative influence on intim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 81 publications
3
16
0
7
Order By: Relevance
“…10,11 Empirical studies have shown that SD has been reported in approximately 50% of kidney transplant patients and has several adverse effects on quality of life. 17 However, compared with male patients, researchers at home and abroad pay far less attention to the FSD and reproductive concerns after KT 16,25,35 ; moreover, a study by Cabral et al 36 found that only 34.6% of female kidney transplant patients referred to discuss sexual issues with their physicians, whereas 73.1% stated it would have been important. These results indicated that more attention and strategies are required from healthcare providers to manage FSD after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Empirical studies have shown that SD has been reported in approximately 50% of kidney transplant patients and has several adverse effects on quality of life. 17 However, compared with male patients, researchers at home and abroad pay far less attention to the FSD and reproductive concerns after KT 16,25,35 ; moreover, a study by Cabral et al 36 found that only 34.6% of female kidney transplant patients referred to discuss sexual issues with their physicians, whereas 73.1% stated it would have been important. These results indicated that more attention and strategies are required from healthcare providers to manage FSD after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…compliance 14 and relationship satisfaction 15 and can be associated with psychological effects (eg, depression). 16 Nevertheless, sexual health is often ignored by health professionals encompassing physicians, nurses, and nephrologists during the consultation, especially after transplantation. 17 In China, the prevalence of chronic kidney disease was estimated to be approximately 10.8%, 18 and ESRD, without treatment, would progress and eventually cause death.…”
mentioning
confidence: 99%
“…In men with chronic kidney disease, vascular, endocrine and neurological problems, drugs used and additional diseases may cause erectile dysfunction and affect sexual functions and reduce libido (25). Studies have shown that renal transplantation leads to endocrine recovery (26) and reduces the incidence of erectile dysfunction (26,27). In our study, it was thought that men had better sexual functions after transplantation for similar reasons.…”
Section: Discussionmentioning
confidence: 50%
“…Evidence suggests that successful kidney transplantation can improve quality of life, life expectancy, and reduce health costs [ 4 ]. However, patients may experience different physical difficulties such as cardiovascular and neurologic complications [ 5 ], sexual dissatisfaction [ 6 ], or mental disorders such as anxiety, depression, or stress [ 7 ]. Patients may also experience postoperative pain, fatigue, and sleep disorders [ 8 ].…”
Section: Introductionmentioning
confidence: 99%